Implementation of Closed Principles in Ad-hoc Arbitration Disputes Settlement by Online Mechanism in Indonesia - Abdullah, Ali; Prasetyo, Yunan; Febrianto, Satria (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
Dispute between the parties at dispute resolution through arbitration in the 1999 Arbitration Law can be simplified in the form of sending a letter, fax, telegram, electronic mail or other alternative type of communication that makes things easier. Meanwhile, according to the provisions in the law, The Arbitration Law 1999 declares that all examinations of disputes by arbitrators or arbitration panels are carried out behind closed doors with the intention that examination of disputes through arbitration upholds the principle of confidentiality. The purpose of this writing is to examine the legal regulations governing online ad-hoc arbitration trials, but confidentiality is maintained. This research was carried out using a normative approach. After the research was executed, there were no arrangements for examinations to be carried out by online ad-hoc arbitration, even though The 1999 Arbitration Law states the examination of the trial decision should be conducted behind closed doors due to the principle of confidentiality.